Assessment of age and sex variability on haematological parameters of indigenous Punganur cattle - P, AVINASH; K, ASWANI KUMAR; B, PUNYA KUMARI (The Indian Journal of Animal Sciences, 2026)
This study aimed to assess the variability of sex and age on the hematological parameters of Punganur cattle. Blood samples were collected from 175 healthy Punganur cattle from Livestock Research Station (LRS), Sri Venkateswara Veterinary University and from farmers in the surrounding areas of Palamaner, Chittoor district, Andhra Pradesh across various age groups (Cows, Bulls, Heifers, Young bulls, Female calves, and Male calves) were collected and analysed. The results were categorized based on sex and age variations. Lymphocyte percentage (P